Gambaran Tingkat Stres Mahasiswa dalam Menghadapi Tugas Akhir di Politeknik Kaltara - Isnina Noor Sakinah (Lembaga Pengembangan Kinerja Dosen, 2023)
Stress is a physical and emotional reaction caused by environmental conditions, physical demands and social conditions that are difficult to control, which requires a person to adjust himself. Stres can happen to everyone, including final year students who are facing their final project. Some of the causes of someone experiencing stres are frustration that can occur when individual efforts to achieve certain goals are hampered or the opportunity to get the desired results is lost. The next cause of stres is a crisis where sudden circumstances can cause stres to individuals. The purpose of this study is to know the description of the stres level of Politeknik Kaltara students in facing their final project. This research uses a descriptive method. Sampling using total sampling technique as many as 67 respondents according to the inclusion and exclusion criteria. Data collection used a stres level questionnaire on students consisting of 14 questions. Based on the results of the study, data were obtained in the form of the highest level of student stres in the mild category 29 (43.3%) respondents, moderate category 22 (32.8%) respondents, severe category 16 (23.9%) respondents. The conclusion of this study shows that the stres level of students who are facing their final project is more in the mild stres category.